Effect of temperature conditions on grain refinement of Mg–Al alloy under ultrasonic field. (2nd November 2017) - Feng, Xiaohui; Zhao, Fuze; Jia, Hongmin; Zhou, Jixue; Li, Yangde; Li, Weirong; Yang, Yuansheng
Abstract: The effects of temperature conditions on the grain refinement of a Mg–Al alloy by ultrasonic treatment were investigated. It was found the grain refinement strongly depended on the temperature. When the ultrasonic treatment was performed above the liquidus temperature, the better grain refinement was achieved in the ingot treated at 700 °C rather than at lower temperature. While for the cases of the ultrasonic treatment being ended below the liquidus temperature, the better refinement can be achieved at lower ending temperature. The undendritic structrue of UST ingots is obviously different with the dendritic structure of UMT ingots. The ultrasonic cavitation improves the nucleation temperature, resulting in greater undercooling to benefit the nucleation. The acoustic streaming accelerates the release of latent heat of solidification and shorten the time for grain growth. Both of the two factors contribute to achieve the grain refinement.